EFFECT OF MO DURING THE OXIDATION OF NI20CR-XMO ALLOYS AT 570°C - Hubby Izzuddin (Metalurgi, 2021)
The effect of Mo addition on the oxidation behavior of the Ni20Cr-xMo alloys at 570°C for 100 h was investigated. The results revealed that oxidation performance of the Ni20Cr alloys was increased by Mo addition. During the oxidation, the Mo-free alloy formed thin NiO scale on the outer scale and thick continous Cr2O3 scale accompanied with inward Cr2O3 penetrations and a Cr-depleted zone. There were also formations of mix Ni-Cr oxides in between NiO and Cr2O3 scale. While, the oxide scales formed on the Mo-containing alloys consisted of a duplex structure with a thick NiO scale on the outer scale and Cr(Mo)-Cr-Mo oxides on the inner scale. A porous oxide structure was also formed in the inner scale. The presence of Mo resulted in the formation of NiO scale and less the inward diffusion into Cr2O3 scale. But, more volatile oxides and porous oxide structures would form with higher Mo addition resulted in lower oxidation resistance for the Ni20Cr alloys.